2018
DOI: 10.1101/338640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual modelling supports the potential for prey detection by means of diurnal active photolocation in a small cryptobenthic fish

Abstract: Active sensing has been well documented in animals that use echolocation and electrolocation. Active photolocation, or active sensing using light, has received much less attention, and only in bioluminescent nocturnal species. However, evidence has suggested the diurnal triplefin Tripterygion delaisi uses controlled iris radiance, termed ocular sparks, for prey detection. While this form of diurnal active photolocation was behaviourally described, a study exploring the physical process would provide compelling… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In clear waters, red light from the sun is the least abundant part of the spectrum (and virtually absent below 15 m of depth) because red light penetrates least through water, but many organisms convert the deeply penetrating green and blue wavelengths into red. Indeed, the eyes of gammarids, a common prey of round goby, strongly reflect red light [122]. An enhanced red perception through an additional red opsin gene may thus be relevant for round goby predation success below 15 m. In turbid waters, red is the most common part of the light spectrum because long wavelengths experience least scattering [24].…”
Section: Environmental Perceptionmentioning
confidence: 99%
“…In clear waters, red light from the sun is the least abundant part of the spectrum (and virtually absent below 15 m of depth) because red light penetrates least through water, but many organisms convert the deeply penetrating green and blue wavelengths into red. Indeed, the eyes of gammarids, a common prey of round goby, strongly reflect red light [122]. An enhanced red perception through an additional red opsin gene may thus be relevant for round goby predation success below 15 m. In turbid waters, red is the most common part of the light spectrum because long wavelengths experience least scattering [24].…”
Section: Environmental Perceptionmentioning
confidence: 99%
“…Using a visual modelling approach, Bitton et al . (2019) showed that the amount of light redirected by a blue ocular spark can indeed generate a perceivable achromatic (luminance) increase in the reflective eyes of gammarid microcrustaceans under natural conditions. Assuming average parameter values of ambient light intensity, ocular spark reflectance and gammarid eye reflectance, average detection distances were in the 1–2 cm range (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, triplefins show more ocular sparks in the presence of prey and change the colour of the ocular spark in response to the colour of the background against which prey is presented, suggesting an association (Michiels et al, 2018). Using a visual modelling approach, Bitton et al (2019) showed that the amount of light redirected by a blue ocular spark can indeed generate a perceivable achromatic (luminance) increase in the reflective eyes of gammarid microcrustaceans under natural conditions. Assuming average parameter values of ambient light intensity, ocular spark reflectance and gammarid eye reflectance, average detection distances were in the 1-2 cm range ( Figure 1).…”
mentioning
confidence: 98%
See 2 more Smart Citations